PENGARUH MEDIA PEMBELAJARAN PUZZLE SEJARAH MELALUI PERMAINAN LEMPAR DADU TERHADAP HASIL BELAJAR SISWA SEJARAH KELAS XI SMAN 4 RUPAT - Salimah, Umi; Bunari, Bunari; Refli Surya Barkara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of dice-rolling as a historical puzzle learning medium on the history learning outcomes of eleventh-grade students at SMAN 4 Rupat. This study used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The study sample consisted of class XI A as the experimental class and class XI B as the control class. Data were collected through pretests and posttests. The results of the hypothesis testing using a t-test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, thus Ha was accepted and Ho was rejected. This indicates a significant effect of using dice-rolling as a historical puzzle learning medium on student learning outcomes. The N-Gain calculation for the experimental class was 62.51%, which is in the moderate category. Thus, dice-rolling as a historical puzzle learning medium is effective in improving the history learning outcomes of eleventh-grade students at SMAN 4 Rupat.